Comparing dislocation force between a flanged haptics IOL and a harpoon haptics IOL - Johannes Zeilinger; Martin Kronschläger; Andreas Schlatter; Natascha Bayer; Oliver Findl (Scientific Reports)
Abstract To compare two different secondary IOL fixation techniques, either flanged or hooked, regarding the least required force to dislocate the haptic in human corneoscleral donor tissue (CST). Experimental laboratory investigation. The least required dislocation force (LRDF) of two different fixation techniques, namely the flanged haptics (FH, as described by Yamane) and the harpoon haptic technique (HH, as described by Carlevale) were investigated using 20 three-piece IOLs (KOWA PU6AS) and 20 single-piece IOLs (SOLEKO CARLEVALE) fixated to human scleral tissue. The main outcome, differences in LRDF of the investigated techniques, was measured with a tensiometer. The dislocation force needed to dislocate the flanged haptics was significantly higher (p < 0.001) in the flanged 3-piece IOL (0.93 ± 0.43 N) than the specialized, harpoon haptics single-piece IOL (0.45 ± 0.18 N). During externalization, breakage occurred in three harpoon haptics. However, no breakage was observed in either haptics during dislocation. The flanged haptic technique proved to be the stronger form of secondary IOL fixation regarding dislocation force in this in vitro study. The harpoon haptics fixation technique showed significantly less resistance to axial traction and a susceptibility to breakage during externalization.